A unique study of post mitral valve surgery status of patients in pre and intra COVID-19 era - Mukhopadhyay, Bhubandeep; Banerjee, P. (International Journal of Research in Medical Sciences, 2022)
Background: In this study we have studied the change of pulmonary artery pressure after mitral valve replacement and closed mitral commissurotomy. We have also correlated pulmonary artery pressure before and after operation with postoperative outcome. Methods: This study was conducted at Department of CTVS of NRS Medical College and Hospitals from August 2019 to September 2021. All 81 patients had rheumatic mitral valve disease. Among these 73 patients underwent mitral valve replacement (MVR) and 8 patients underwent closed mitral commissurotomy (CMC). Group 1 (n=35) consisted of patients who underwent MVR having preoperative systolic PAP measured by TTE was less than 50 mmHg. Group 2 patients (n=38) had preoperative systolic PAP more than or equal to 50 mmHg measured by TTE. Group 3 patients (n=8), consists of patients who underwent CMC. Compared the results between group 1 and 2 and documented the results of group 3 separately. Results: Our results showed a significant decrease in SPAP after MVR, and further fall of SPAP in the immediate and late postoperative period. Conclusions: In conclusion, PAP returns to near-normal values after MVR in patients with severe preoperative PAH and to normal values in patients with mild preoperative PAH. Reductions in PAP in patients with preoperative PAH occur immediately after MVR. Postoperative period of patients with severe PAH may be hectic. CMC may be a valid option in isolated MS in selected patients and is very much cost-effective. There were no differences noted among the types of valves used.